Atypical hand, foot, and mouth disease in an adult patient - Merzel Šabović, Eva Klara (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2019)
Hand, foot, and mouth disease is a highly contagious disease that predominantly affects children under the age of five. The illness is much less common in adults and often presents with atypical skin lesions. Here we describe the case of a 19-year-old healthy, immunocompetent male patient with atypical clinical presentation, with a macular rash on the scalp, palms, soles, and shins, and with minimal lesions in the oral cavity. The diagnosis of hand, foot, and mouth disease was confirmed by isolation of coxsackievi-rus A6 from a vesicle smear obtained on the right sole. The skin lesions resolved spontaneously in 1 week. This case emphasizes the underestimated fact that hand, foot, and mouth disease can also occur in adults, in either typical or frequently atypical form, and it highlights the role of coxsackievirus A6. Together with the case presentation, a review of the literature describing the dis-ease in adults is presented.
Keywords: bolezni rok, slinavke in ust; coxsackievirus A6; enterovirus; hand, foot, and mouth disease